Southeast Research and Extension Center Agricultural Research 2020 (Kansas Agricultural Experiment Station Research Reports, 2020)
Research report for the Southeast Research and Extension Center, Kansas State University, 2020
Keywords: beef cattle; soil; water management; cropping systems